Phagocytosis of 2-hydroxyethylmethacrylate copolymer particles by different types of macrophages - Vĕtvicka, V; Fornůsek, L; Kopecek, J; Prikrylová, D (Folia biologica, 1983)
Phagocytic activity (for 2-hydroxyethylmethacrylate particles) in normal and thioglycollate- or proteose peptone-stimulated peritoneal macrophages, Peyer's patches macrophages, bone marrow macrophages and macrophage-like cell lines BWM, DCH 5, PU-5-lR and RAW 264.7, in suspension and after adherence to a substrate, was tested. Results of testing showed that 2-hydroxyethylmethacrylate particles are advantageous for following the phagocytic activity of the above cell types.
Keywords: myši; makrofágy; kultivované buňky; Cells, Cultured; Macrophages; Methacrylates; buněčná adheze; Phagocytosis; Cell Adhesion; zvířata; Mice; methakryláty; fagocytóza; Animals